Randomized Controlled Pilot Study of B Cell–Targeted Induction Therapy in HLA Sensitized Kidney Transplant Recipients. Issue 12 (13th November 2013) - Ejaz, N. S.; Shields, A. R.; Alloway, R. R.; Sadaka, B.; Girnita, A. L.; Mogilishetty, G.; Cardi, M.; Woodle, E. S.
Abstract Optimal induction regimens for patients at high risk for antibody and/or cell–mediated rejection have not been established. This pilot, prospective, randomized study evaluated addition of B cell/plasma cell–targeting agents to T cell–based induction with rabbit antithymocyte globulin (rATG) in high immunologic risk renal transplant recipients. Patients were randomized to induction with rATG, rATG + rituximab, rATG + bortezomib or rATG + rituximab + bortezomib. Inclusion criteria were: (1) current cytotoxic panel reactive antibody (PRA) ≥20% or peak cytotoxic PRA ≥50% or (2) T or B cell positive flow crossmatch with donor‐specific antibody (DSA) or (3) historical positive serologic or cytotoxic crossmatch or DSA to donor or (4) prior allograft loss with more than one acute rejection. Median overall follow‐up was 496 days: 1‐year and overall acute rejection were 25% and 27.5%, and 25% of patients developed de novo DSA within 1 year. One‐year and overall patient survival were 97.5% and 92.5%, and 1‐year and overall death‐censored allograft survival were 97.5% and 95%. Renal allograft function posttransplant was similar among all arms. Eight of nine cases of peripheral neuropathy were mild, whereas one case was moderate and required a narcotic prescription. In conclusion, addition of rituximab and/or bortezomib to rATG induction has an acceptable safety/toxicity profile in a high immunologic risk renal transplant population.